Magnetic resonance imaging of myocardial strain: A review of current approaches. Issue 5 (4th May 2017) - Chitiboi, Teodora; Axel, Leon
Abstract : Contraction of the heart is central to its purpose of pumping blood around the body. While simple global function measures (such as the ejection fraction) are most commonly used in the clinical assessment of cardiac function, MRI also provides a range of approaches for quantitatively characterizing regional cardiac function, including the local deformation (or strain) within the heart wall. While they have been around for some years, these methods are still undergoing further technical development, and they have had relatively little clinical evaluation. However, they can provide potentially useful new ways to assess cardiac function, which may be able to contribute to better classification and treatment of heart disease. This article provides some basic background on the physical and physiological factors that determine the motion of the heart, in health and disease and then reviews some of the ways that MRI methods are being developed to image and quantify strain within the myocardium. Level of Evidence: 4 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2017;46:1263–1280.